Propolis mouthwashes efficacy in managing gingivitis and periodontitis: a systematic review of the latest findings - Muhammed Al-Huda Ballouk; Mohamed Altinawi; Abeer Al-Kafri; Talar S. Zeitounlouian; Piotr S. Fudalej (BDJ Open)
Abstract Background and objectives Gingivitis and periodontitis are common periodontal diseases that can significantly harm overall oral health, affecting the teeth and their supporting tissues, along with the surrounding anatomical structures, and if left untreated, leading to the total destruction of the alveolar bone and the connective tissues, tooth loss, and other more serious systemic health issues. Numerous studies have shown that propolis can help reduce gum inflammation, inhibit the growth of pathogenic bacteria, and promote tissue regeneration, but with varying degrees of success reported. For this reason, this comprehensive systematic review aims at finding out the truth concerning the efficacy of propolis mouthwashes in treating gingivitis and periodontitis, as its main objective. Data sources Research findings from 6 different databases: China National Knowledge Infrastructure (CNKI), PubMed®, Europe PMC, Cochrane Central Register of Controlled Trials (CENTRAL), BioMed Central, and Google Scholar, were retrieved and examined in addition to a manual search in the references lists. Study selection and synthesis The PICOS framework was used to select and exclude studies. The focus was on clinical randomized controlled trials (RCTs) that examined the effectiveness of propolis-containing mouthwashes in comparison with propolis-free ones for the treatment of gingivitis and periodontitis, employing related periodontal indices. Animal studies, microbiological studies, in-vitro studies, retrospective studies, case-control studies, cohorts, case reports, case series, reviews, letters, editorials, meta-analyses, and non-clinical randomized controlled trials (non-RCTs), all were excluded. A meta-analysis was not performed and data were only studied qualitatively due to the obvious heterogeneity amongst the studies. Data from the selected studies were extracted, and then the revised Cochrane’s risk of bias tool (RoB 2.0) was utilised by two of the authors, independently, to evaluate the risk of bias in each study. Results At first, 151 results were reached, but then after removing duplicates, 99 records remained, and were later screened, assessed, and studied in full details based on the set PICOS criteria. Out of these 99 articles, ten studies were included in this systematic review, encompassing a total of 453 patients with an age range of (13–70) years old. Propolis mouthwashes with different protocols of application were the intervention whereas placebo or the rest of the tested mouthwashes such as, chlorhexidine, sodium fluoride with cetylpyridinium chloride, sterile distilled water, hydrogen peroxide, were the ones to which propolis mouthwashes were compared. Treatment duration extended from 14 days to 3 months and the follow-up period differed from 14 days to 3 months. In general, propolis mouthwashes decreased plaque accumulations and gingival inflammation in gingivitis patients based on the employed indices. On the other hand, the aforementioned tested mouthwashes other than propolis were deemed equally effective or even superior to propolis in some studies. As an overall assessment for the risk of bias, four studies were assigned as having a low risk of bias. Two studies were deemed to have some concerns, while four studies were identified as having a high risk of bias. Conclusions Despite the fact that propolis has shown positive effects in terms of controlling gingival and periodontal inflammation especially when used with mechanical methods, studies lack certainty and their power of evidence is low with no agreed gold standards. These conclusions come, for sure, within the limitations of this review, like having substantial variability amongst the included studies and the presence of studies with a high risk of bias. The findings demonstrate that propolis-based mouthwashes showed promising clinical outcomes in reducing plaque and gingival inflammation. However, it is highly recommended to conduct more rigorous trials with patient-reported outcome measures, extended follow-up periods, larger samples sizes, better-designed methodologies, typified propolis use, and with the implementation of similar indices in order to obtain more reliable, conclusive, and generalisable results. Prospero Registration Number CRD42024524523.